Analisis Penentuan Lokasi Gangguan Hubung Singkat Pada Saluran Transmisi Di Sulawesi Tenggara - Pebi Wahyudin; Mustarum Musaruddin; Hasmina Tari Mokui (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2022)
The electricity system often experiences disturbances, especially short circuit disturbances on transmission lines. This short circuit disturbance is caused by various things such as lightning surges, fallen trees, animals, and other conditions. The interconnected Southeast Sulawesi power system cannot be separated from this short circuit problem. Therefore, determining the location of this short-circuit fault must be done quickly so that the cause of the disturbance can be immediately identified. This study aims to analyze the determination of the location of short circuit faults using the Takagi Method. Simulations were carried out using ETAP 16.0.0 software to see the condition of the Southeast Sulawesi system power flow. This Takagi method analyzes the location of the disturbance using the conditions before and after the disturbance occurs based on the recorded data at the substation. The results of the analysis carried out on the Southeast Sulawesi transmission line show that the percentage of accuracy in determining the location of a single-phase short-circuit fault to ground using the Takagi method is better, with a distance difference of 0.368-0.581 km (1.49%) when compared to the reading results on recordings of 10,173-9,960 km (31.58%) from the fault location occurred after inspection of the Lasusua-Kolaka transmission line. Disturbances on lines 1 and 2 Kolaka-Lasusua produce an error value of 1.533 km (9.24%) and 1.547 km (9.32%) when compared to fault locator readings of 3.212 km (19.36%) and 1.812 km ( 10.92%). Meanwhile, the Unaaha-Kolaka transmission line produces a distance difference of 0.709 km (3.29%) when compared to the fault locator reading of 4.323 km (20.12%). The results of the power flow simulation produce an installed generating capacity of 188 MW, a total active power of 116.780 MW and a reactive power of 29,944 Mvar. Thus, it can be concluded that the Takagi Method has a better accuracy value in reading fault locators.